RESPON DAN KESIAPAN PEMERINTAH KOTA BALIKPAPAN MENGENAI TERBITNYA PERATURAN PEMERINTAH NOMOR 51 TAHUN 2009 TENTANG PEKERJAAN KEFARMASIAAN - , Wiwi Erwina; , Prof. Dr. Dra. Sri Suryawati, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The Government Regulation Number 51 of 2009 is government regulations governing the duties and authority of pharmacists in a pharmaceutical works. This regulation also expects that pharmacists can perform the duties and authorities in accordance with the development of science and technology and legislation applicable. To find out how the Balikpapan city government's responsiveness and readiness on the issuance of government regulation number 51 of 2009, it can be seen from the development of human resources, in this case the resources of pharmacists in health centers by reference to 3 (three) components of human resource development by the WHO, 1) Education and Training, 2) Career Development, 3) cooperation of interrelated institutes Research Methods: The study is a descriptive analytic study. The data were collected through interviews and observations of related documents. Using the theoretical approach to human resource development of the national drug policy guidelines by the WHO, which are measured through several components, namely education and training, career development, and cooperation of interrelated institutes. Results: The city of Balikpapan has 26 health centers, the last survey was on December 2010, out of 26 health centers, 13 health centers have had a pharmacist, so the numbers of pharmacists in health centers are 14 pharmacists. Based on the response and readiness of the education and training, education and training will be held in the form of seminars and training workshops. From the response and readiness of career development planning on the pharmacist recruitment, it is expected to be 100%. From the response and readiness of cooperation of interrelated institutes, a cooperation with IAI of Balikpapan branch will be conducted Conclusion: The government of Balikpapan city responds well and is ready to implement regulations on the issuance of government regulation number 51 of 2009 on the pharmaceutical works.